Analisis SWOT, Value for Money, dan Pareto Optimum Pengadaan Langsung Barang/Jasa di BLU UIN STS Jambi - Pantun Bukit; Hana Tamara Putri; Saiyid Syekh; R. Adisetiawan (Universitas Batanghari, 2022)
Change of Status from PTN-Satker to PTN-BLU, then through the Decree of the President of the Republic of Indonesia Number 37 of 2017 dated April 3, 2017, IAIN Sulthan Thaha Saifuddin Jambi officially transformed into UIN Sultan Thaha Saifuddin Jambi. This fundamental change certainly has an impact on changing the paradigm and mindset of organizational governance as a Public Service Agency on the one hand and the University on the other. The process of metamorphosis of the Institute into a University has opened up opportunities for the opening of new and general study programs at UIN Sulthan Thaha Saifuddin Jambi, this is a potential in providing quality educational services that are relevant to the needs of the community. Based on the SWOT Analysis, which is analyzed from the aspects of strengths, weaknesses, opportunities and challenges, it can be formulated so strategy (using strengths to get opportunities, ST strategy (using strengths to overcome threats), WO strategy (correcting or overcoming weaknesses to get opportunities) and WT Strategy (correcting weaknesses to overcome threats. From these four strategies, one main strategy emerged, namely the direct procurement method with a nominal limit of Rp. 500 million with more transparency, accountability and professionalism, so that in turn this direct procurement method becomes more efficient, effective and optimal. Based on the results of the Value For Money analysis of revenue and budget realization of BLU UIN STS Jambi in 2017-2019, from the Economic Ratio the criteria for three economic years, from the Efficiency ratio in 2017-2018 is efficient, 2019 is inefficient, from the Effectiveness ratio in 2017-2018 is effective and 2019 is ineffective. Based on the Pareto Chart analysis, it was found that there were two problems or 25 percent of the root of the problem that caused more than 80 percent of the problems to achieve optimal pareto during 2017-2019 in the direct procurement method below Rp. 200 million, namely first the number of packages was too much, so that it became uneconomical, and the second was an incidentally planned work package, so that the output became less effective. The incidental work package arises because the threshold income is only known to be the amount in September-October (Special income from Student Tuition) every year, so the time is very short to tender.